Hatred of sex - Davis, Oliver, 1977-; Dean, Tim (Provocations (Lincoln, Neb.), 2022)
Draws on Jacques Rancière's thesis in Hatred of Democracy to help explain the aversion to sex that is evident in numerous forms in the culture around us.